Pretreatment Nomograms for Local and Regional Recurrence after Radical Radiation Therapy for Primary Nasopharyngeal Carcinoma - Chen, Fo-ping (J Cancer, 2017)
Background: The aim of this study was to build nomograms to predict local recurrence (LR) and regional recurrence (RR) in patients with nasopharyngeal carcinoma (NPC) underwent intensity-modulated radiation therapy (IMRT). Patients and Methods: A total of 1811 patients with non-metastatic NPC treated with IMRT (with or without chemotherapy) between October 2009 and February 2012 at our center were involved for building the nomograms. Nomograms for LR-free rate and RR-free rate at 3- and 5- year were generated as visualizations of Cox proportional hazards regression models, and validated using bootstrap resampling, estimating discrimination and calibration. Results: With a median follow up of 49.50 months, the 3- and 5- year LR-free rate were 95.43% and 94.30% respectively; the 3- and 5- year RR-free rate were 95.94% and 95.41% respectively. The final predictive model for LR included age, the neutrophil/leukocyte ratio (NWR), pathological type, primary gross tumor volume, maxillary sinus invasion, ethmoidal sinus invasion and lacerated foramen invasion; the model for RR involved NWR, plasma Epstein-Barr virus (EBV) DNA copy number, cervical lymph node volume and N category. The models showed fairly good discriminatory ability with concordance indices (c-indices) of 0.76 and 0.74 for predicting LR and RR, respectively, as well as good calibration. The proposed stratification of risk groups based on the nomograms allowed significant distinction between Kaplan-Meier curves for LR and RR. Conclusions: The proposed nomograms resulted in more-accurate prognostic prediction for LR and RR with a high concordance, hence to inform patients with high risk of recurrence on more aggressive therapy. The prognostic nomograms could better stratify patients into different risk groups.